Perbandingan pendirian dan sistem hukum perusahaan antar negara indonesia dan kamboja - Saputro, Mahardyan Trymario (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
With the existence of a company as a business entity in the business world between Indonesia and Cambodia, it makes the arrangement of company establishment an initial concern. In Indonesia, a Company is a legal entity that is a capital partnership, established based on an agreement, carrying out business activities with capital, established based on an agreement, conducting business activities with an authorized capital wholly divided into shares and complying with the requirements stipulated in this Law and its implementing regulations. A Cambodia limited liability company (LLC) is managed by officers and directors and is funded by capital provided by the shareholders. It can be as small as a single business person or as large as a business with many shareholders. Companies provide a framework for businesses to own property, sign contracts, and engage in legal action without putting the assets of their shareholders at risk.